Fertility Enhancement but Premature Ovarian Failure in esr1-Deficient Female Zebrafish - Chen, Yu; Tang, Haipei; Wang, Le; He, Jianan; Guo, Yin; Liu, Yun; Liu, Xiaochun; Lin, Haoran (Frontiers in Endocrinology, 2018)
It is well established that estrogens regulate female reproduction through estrogen receptors (ERs) in the ovary. However, the precise physiological role of estrogen/ER signaling in reproduction processes remains poorly defined in zebrafish. In this study, we successfully generated an ERα (esr1) mutant line in zebrafish via transcription activator-like effectors nucleases (TALENs). It was found in the mutant females that the fertility was enhanced and the ovarian histology was normal at 90 days post-fertilization (dpf). However, the number of fertile females decreased with age. By 180 dpf, esr1 mutant females were infertile with degenerated ovaries, while the age-matched wild-type females were still fertile. Additionally, few large vitellogenic granules can be found in full grown (FG) follicles at 90 dpf and the expression of vtg genes were down-regulated at both 90 and 180 dpf in esr1 mutant zebrafish. Moreover, steroidogenesis pathway and mTOR signaling pathway were over-activated at 90 dpf, but declined prematurely in esr1 mutant zebrafish by 180 dpf. Collectively, the present study provides evidences that esr1 is fundamental for ovarian maintenance in zebrafish.